Assessing Breastfeeding Attitudes and Self‐Efficacy Among Health care Personnel and Women With Multiple Sclerosis: Two Cross‐Sectional Surveys - Solange M. Saxby; Carlyn Haas; Anna Klein; Tyler J Titcomb; Farnoosh Shemirani; Terry Wahls; Linda Snetselaar; Christine Gill; Pamela Mulder (Brain and Behavior)
ABSTRACT Introduction This study aimed to describe breastfeeding attitudes among health care personnel, as well as breastfeeding attitudes and self‐efficacy in women with multiple sclerosis (MS), who are currently or have previously breastfed. Methods Two cross‐sectional surveys were sent electronically to health care personnel at a single center to capture attitudes toward breastfeeding in women with MS using the Iowa Infant Feeding Attitudes Scale (IIFAS), and women with MS who were currently or had previously breastfed to measure breastfeeding attitudes and self‐efficacy using the IIFAS and Breastfeeding Self‐Efficacy Survey‐Short Form (BSES‐SF). Descriptive statistics and one‐way analysis of variance were used to assess differences among categories of participant demographics. Results In the health care personnel survey, among health care specialties, neonatology exhibited the highest mean scores on the IIFAS (69.8 ± 8.89), reflecting positive attitudes, while neurology and students had the lowest mean IIFAS scores (62.4 ± 10.3 and 58.2 ± 3.94, respectively) with neutral attitudes. Health care personnel with 16 or more years of service demonstrated positive attitudes toward breastfeeding (70.9 ± 9.30), as assessed by IIFAS. In the survey of women with MS, women identifying as Middle Eastern/North African had the highest mean IIFAS score (78.0 ± 5.66), indicating positive breastfeeding attitudes, while women identifying as Black had the lowest (62.7 ± 6.07), reflecting a neutral attitude. Positive attitudes were revealed by participants who exclusively breastfed for 6 months (70.1 ± 7.17) and who had three or more children (70.1 ± 6.17). Participants who exclusively breastfed for 6 months and who had breastfed three or more children demonstrated the highest breastfeeding self‐efficacy as assessed by BSES‐SF scores (52.2 ± 4.93 and 51.7 ± 5.26, respectively). Discussion Attitudes towards breastfeeding in women with MS differed by health care specialty and years of service in health care personnel. Among women with MS, infant feeding attitudes and breastfeeding self‐efficacy varied based on ethnicity, age, number of children, number of children breastfed, and breastfeeding exclusivity.